Interactive effects of rice bran compost and chemical fertilizers on macronutrients, oil and protein content in sunflower (Helianthus annuus L.) - Alauddin, M; Mohsin, GM; Ali, AHMZ; Rahman, MK (International Journal of Agricultural Research, Innovation and Technology, 2021)
A field experiment was conducted at the research farm of Charfasson Govt. College, Bhola, Bangladesh in rabi season in 2015-2016 to evaluate the impact of conjunctive use of chemical fertilizers with rice bran on concentration, uptake and seed quality of sunflower cv. BARI-2 (Keroni-2). The experiment was laid out in the randomized complete block design (RCBD) having sixteen treatments with three replications. The size of the plots were 3 m x 2 m. Treatments were T1 Control (- RB and -NPK), T2: 2.5 t RB ha-1, T3: 5.0 t RB ha-1,T4: 7.5 t RB ha-1, T5: N40P30K50 kg ha-1,T6: N80P60K100 kg ha-1, T7: N120P90K150 kg ha-1, T8: 2.5 t RB ha-1 + N40P30K50 kg ha-1, T9: 2.5 t RB ha-1 + N80P60K100 kg ha-1, T10: 2.5 t RB ha-1 + N120P90K150 kg ha-1, T11: 5.0 t RB ha-1 + N40P30K50 kg ha-1, T12: 5.0 t RB ha-1 + N80P60K100 kg ha-1, T13: 5.0 t RB ha-1 + N120P90K150 kg ha-1, T14: 7.5 t RB ha-1 + N40P30K50 kg ha-1, T15: 7.5 t RB ha-1 + N80P60K100 kg ha-1, T16: 7.5 t RB ha-1 + N120P90K150 kg ha-1. Results showed that the concentration, uptake and quality of seeds (oil and protein) of the crop increased with increasing rate of the amendments significantly (P<0.05) over the control and the variation between the treatments were also significant irrespective of the sources of amendments in most of the cases. Generally, combination of the treatments showed better performance than their individual application. Maximum values of NPKS concentration (%) in different organs of sunflower were 1.22, 0.35, 1.90, 0.18 for stem; 1.17, 0.35, 2.41, 0.16 for root; 3.98, 0.43, 4.28, 0.24 for leaf, 1.04, 0.65, 3.00, 0.22 for petiole; 2.16, 0.58, 2.21, 0.26 for inflorescence and 5.24, 0.83, 1.60, 0.47 for seed measured in treatments 5.0 t RB ha-1 + N120P90K150 kg ha-1 and 7.5 t RB ha-1 + N120P90K150 kg ha-1 in most of the cases. However, their uptake pattern also followed the same trend as in concentration and the highest values were found in those treatments in most of the cases. Significantly (P<0.05%) the highest content of oil (51.1%) in seed was measured in the treatment 5.0 t RB ha-1 + N120P90K150 kg ha-1 and protein (33.9%) was found in the treatment 5.0 t RB ha-1 +N80P60K100 kg ha-1. Their lowest values were found in control for oil and in 2.5 t RB ha-1 for protein, which was lower than control treatment. The overall findings of this study indicated that rice bran in combination with chemical fertilizers could be applied to achieve better concentration and uptake in different organs, oil and protein content in seeds of sunflower. Int. J. Agril. Res. Innov. Tech. 10(2): 91-99, December 2020